2022
DOI: 10.1021/acsomega.1c06551
|View full text |Cite
|
Sign up to set email alerts
|

Semen Proteomics of COVID-19 Convalescent Men Reveals Disruption of Key Biological Pathways Relevant to Male Reproductive Function

Abstract: A considerable section of males suffered from COVID-19, with many experiencing long-term repercussions. Recovered males have been documented to have compromised fertility, albeit the mechanisms remain unclear. We investigated the impact of COVID-19 on semen proteome following complete clinical recovery using mass spectrometry. A label-free quantitative proteomics study involved 10 healthy fertile subjects and 17 COVID-19-recovered men. With 1% false discovery rate and >1 unique peptide stringency, MaxQuant ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 66 publications
1
27
0
Order By: Relevance
“…Besides, the association of CST3 with S100A9 also indicates a correlation between monocyte-mediated inflammatory response and HRCT score, which supports our previous findings. We also found a strong association between HRCT score and PSAP, a gene involved in antigen presentation and male fertility, both are perturbed in severe COVID-19 patients (47,48).…”
Section: Distinct Immune Response Signatures As Revealed By Similarit...supporting
confidence: 54%
“…Besides, the association of CST3 with S100A9 also indicates a correlation between monocyte-mediated inflammatory response and HRCT score, which supports our previous findings. We also found a strong association between HRCT score and PSAP, a gene involved in antigen presentation and male fertility, both are perturbed in severe COVID-19 patients (47,48).…”
Section: Distinct Immune Response Signatures As Revealed By Similarit...supporting
confidence: 54%
“…Return to normal sperm morphology values is observed with increasing time after recovery ( Guo et al , 2021a ; Donders et al , 2022 ; Hu et al , 2022 ). Emerging evidence showed that key biological pathways relevant to male reproductive function are disrupted in COVID-19 convalescent men ( Ghosh et al , 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…While most published studies analyzed in this research area have focused on the following specimen types: blood samples, including serum [11][12][13][14][15][16][17][18][19][20][21] , plasma 12,13,[22][23][24][25][26][27][28][29][30][31][32] , and peripheral blood mononuclear cells (PBMC) 33,34 , there are also studies analyzing FFPE tissue 35,36 , urine [37][38][39][40][41] , fecal 42 , sputum 23 , extracellular vesicle 43,44 , cerebrospinal fluid 21 , semen 45 , colostrum 46 , colostrum 47 and nasopharynx swabs samples 48 . All these studies have provided proteomic snapshots of different aspects of tissues from COVID-19 patients.…”
Section: Introductionmentioning
confidence: 99%